2002
DOI: 10.1006/bcmd.2002.0505
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-6-phosphate Dehydrogenase Deficiency in Portugal: Biochemical and Mutational Profiles, Heterogeneity, and Haplotype Association

Abstract: Glucose-6-phosphate dehydrogenase (G6PD) deficiency is the most common human enzymopathy. This deficiency in erythrocytes has a prevalence of 0.51 Ϯ 0.109 in the Caucasoid male population of Portugal. The frequency for deficiency-conferring genes is 0.39% in the Portuguese population. In the herein study populations males from areas of Portugal presenting with the highest prevalence of G6PD deficiency (Castelo Branco, Setúbal, Faro, and Lisbon) as well as similar subjects located in the border Center/North are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…We performed Sequenom analyses for all sites (primers in Table 2). Additionally, for the T968C polymorphism, we amplified the surrounding region (forward primer: CATC TGTGGCCACAGTCATC; reverse primer: TGGTCATCA TCTTGGTGTAC, T annealing = 57 C), digested the amplified fragments using the MspI restriction enzyme (New England Biolabs, Ipswich, MA) as described in the work by Rodrigues and others, 16 and confirmed that it remains a valid genotyping approach in resource-limited settings. Amplification reactions were performed with Taq Platinum according to the manufacturer's protocols (Invitrogen/Thermo Fisher Scientific, Waltham, MA).…”
mentioning
confidence: 55%
“…We performed Sequenom analyses for all sites (primers in Table 2). Additionally, for the T968C polymorphism, we amplified the surrounding region (forward primer: CATC TGTGGCCACAGTCATC; reverse primer: TGGTCATCA TCTTGGTGTAC, T annealing = 57 C), digested the amplified fragments using the MspI restriction enzyme (New England Biolabs, Ipswich, MA) as described in the work by Rodrigues and others, 16 and confirmed that it remains a valid genotyping approach in resource-limited settings. Amplification reactions were performed with Taq Platinum according to the manufacturer's protocols (Invitrogen/Thermo Fisher Scientific, Waltham, MA).…”
mentioning
confidence: 55%
“…There are a wide variety of G6PD deficiency associated mutations in the Portuguese population (7). In this study we report a new mutation in the G6PD gene that gives rise to a mild enzymatic deficiency in an individual from the island of Flores of the Azorean archipelago.…”
Section: Introductionmentioning
confidence: 78%
“…Higher frequencies were detected among Palestinians in the Gaza Strip [8] and in Tunisia [6]. Moreover, we searched for the Mediterranean allele in the Angolan sample since there are historical references to European populations having settled in Angola, in particular the Portuguese, where this mutation is prevalent [7]. However, we did not encounter the allele in our sample.…”
Section: Discussionmentioning
confidence: 96%
“…These variants reflect allelic genes located in the long arm of the X chromosome (Xq28) resulting in an X-linked recessive mode of inheritance [7,8]. More than 160 mutations have been identified as responsible for the deficiency, the majority of them consisting of single point mutations causing the replacement of amino acids [6].…”
Section: Introductionmentioning
confidence: 99%